Aesthetics of the Artistic Construction in Educational TV Programs " progrm Hello Hi! A Model": محمد عبد الرضا حسين (Al-Academy, 2021)
The TV has the ability to combine sound and picture, which makes it of a direct impact on the recipient as it is a rich communicative tool with various artistic forms that display through this small screen programs and films, so that the TV has become superior over many other means of communication. This research is concerned with the technical and artistic ability in the production of programs owned by the TV as a means of attraction of educated children aged between 5-12 years old, which makes it an educational supplement for the school that helps them in providing knowledge, acquiring skills and being informed about the different sciences through educational programs. It is known that the child at this stage enjoys when watching certain kinds of these programs. As what most attracts the child's attention is the motion picture and the sound and visual effect, in addition to the cartoon films, Muppets, color, flashiness of lights, and the talking stories in the voices of animals and birds. The industry of educational programs for children must be well educationally prepared through employing the artistic and technical forms that help the child to understand the proposed material or information smoothly. This is the research axis that ends with some pivotal results including that digital technology played a significant role in solving the problems and giving a space for attracting children through the movement, color and effects. Colors represented the identity of the program as it has been employed in a unified way along the series of the program that it got linked in color even with the intervals.